Carboxamide-Accelerated Chemoselective Borylation of Iodoarenes under Photoirradiation - Nakashima, Yusei; Sumimoto, Michinori; Nishikata, Takashi (Synthesis, 2023)
Borylation of haloarenes is one of the most important methodologies to synthesize borylated arenes. Generally, borylation of haloarenes occurs smoothly at the sterically less hindered para or meta position by the use of a transition metal catalyst or a photoredox catalyst or under basic conditions. This study reports on the ortho-specific and chemoselective borylation of ortho-iodoarene possessing carboxamide under visible-light irradiation. When a haloarene containing both C–I and C–X bonds is employed as a substrate, another C–X bond (not ortho) remains intact during the reaction. Mechanistic studies revealed that the key to the success of this reaction is the generation of a diboron-bridged five-membered ring as a transition state, in which the diboron-bridged five-membered ring and the benzene ring in the transition state are perpendicular to each other, owing to steric repulsion by the iodine atom at the ortho position. This chemoselectivity is suitable for the synthesis of borylated building blocks.
Keywords: borylation; ortho-specific; chemoselective; photoredox reactions